Hypersexuality in a rape victim child - Shibraumalisi, Nur Amirah; Zainal Abidin, Mohd Hafidzudin; Al Kuddoos, Nabil Muhammad; Yusof Khan, Abdul Hanif Khan (Universiti Putra Malaysia, 2021)
Hypersexuality is rare in children. Our case describes a 14-year-old girl who presented with a history suggestive of hypersexuality. She was repeatedly raped and exposed to video pornography at a very young age. Consequently, she became addicted to pleasure during sexual intercourse and actively involved in multiple unprotected sexual intercourses. Management, in this case, was challenging, where early intervention with contraceptive methods and cognitive behavioural therapy were unsuccessful. Subsequently, alternative treatment with Islamic psycho-spiritual therapy combined with conventional therapy resulted in an improvement in her sexual pre-occupation. This case highlights the importance of recognition of hypersexuality, especially among children with a history of sexual abuse as management proofs to be challenging, and requires a multimodal approach to prevent a potentially devastating outcome.